Mumps virus induces innate immune responses in mouse ovarian granulosa cells through the activation of Toll-like receptor 2 and retinoic acid-inducible gene I. (15th November 2016) - Wang, Qing; Wu, Han; Cheng, Lijing; Yan, Keqin; Shi, Lili; Zhao, Xiang; Jiang, Qian; Wang, Fei; Chen, Yongmei; Li, Qihan; Han, Daishu
Abstract: Mumps virus (MuV) infection may lead to oophoritis and perturb ovarian function. However, the mechanisms underlying the activation of innate immune responses to MuV infection in the ovary have not been investigated. This study showed that Toll-like receptor 2 (TLR2) and retinoic acid-inducible gene I (RIG-I) cooperatively initiate innate immune responses to MuV infection in mouse ovarian granulosa cells. Ovarian granulosa cells infected with MuV significantly produced pro-inflammatory cytokines and chemokines, including interleukin-1β (IL-1β), tumor necrosis factor α (TNF-α), monocyte chemotactic protein 1 (MCP-1), and type 1 interferons (IFN-α and IFN-β). Knockdown of RIG-I significantly decreased MuV-induced cytokine expression. TLR2 deficiency reduced the expression of IL-1β, TNF-α, and MCP-1 but did not affect the expression of IFN-α and IFN-β in granulosa cells after infection with MuV. Intraperitoneal injection of MuV induced the ovarian innate immune responses in vivo, which suppressed estradiol synthesis and induced granulosa cell apoptosis. The results provide novel insights into the mechanisms underlying MuV-induced innate immune responses in the mouse ovary. Highlights: Mumps virus (MuV) infects mouse ovarian granulosa cells. MuV infection induces innate immune responses in granulosa cells through the activation of TLR2 and RIG-I. Intraperitoneal injection of MuV suppresses estradiol synthesis and induces the apoptosis of granulosa cells.